Reverse Transcriptase in Situ Expression Patterns of P53, Cyclin E And Rb Genes at Different Stages of Breast Cancer - Zamanian, Mohammadreza (2007)
Breast cancer is one of the most important health problems among females. One of the most important challenges regarding breast cancer diagnosis and treatment is the precise clinical staging of the disease. With regards to the selection of appropriate treatment method, identifying the lymph node involvement by cancerous cells is a major determinant. Until now, many attempts have been made to find stage specific molecular markers to help the clinicians make precise staging of the disease. Through this, evaluating the activity of some important genes in cancer evolution and progression seems to be the most sensible step in this direction. p53, Cyclin E and Rb are genes that are mostly interactive in cell cycle regulation and cell division as well, has been shown to have an important role in cancer development particularly in breast cancer. Abnormalities in their inhibitory and or stimulatory roles in cell cycle progression can lead cells to enter hyperproliferative or neoplastic states. Therefore, assessments to determine their activity can lead to finding any differences in their expression levels between benign and malignant breast tissues, as well as different stages of breast cancer.In the present study we have used Reversed Transcriptase in situ Polymerase Chain Reaction (RT in situ PCR) in order to determine p53, Cyclin E and Rb mRNA expressions in different human breast samples including benign and malignant tissues. This method allows detection of very low copies ofmRNA at cellular level. In the current study, the presence of p53, Cyclin E and Rb mRNA expressions were investigated in 17 cases of human breast tissues, which were donated as paraffin embedded materials by the pathology ward of Milad hospital, located in Tehran, Iran. We divided the samples into four groups based on their pathology reports. Five samples in each first group as named; non-malignant human breast lesions or NM, lymph node negative human breast cancer (No regional lymph node involvement; LNN) and lymph node positive human breast cancer (Positive for regional lymph node involvement; LNP). There were just two samples available in the fourth group of our study as extra nodal metastatic human breast cancer (Positive for distant metastasis; MB). Our data analysis was mostly based on qualitative assessment of the images which includes the presence of expression in tissue sections as well as the location of the signals throughout the tissue and inside the cells. In addition, we did statistical analysis to compare the abundance of expression among different categories of our samples. Analysis of the data showed that the closest results to significant level «0.05) were those comparing benign and malignant groups especially for Rb .mRNA. While, the most improbable results to significant level were those comparing among four study groups especially between LNP and MB.Our findings demonstrated a dominant presence of p53 and Cyclin E mRNA expression in malignant breast tissues as compared to benign lesions. On the contrary_ benign breast lesions showed a more dominant expression of Rb mRNA than malignant tissues. A companson between different breast cancer groups in our study showed slight differences in the proportions and intensities of p53, Cyclin E and RB mRNA expreSSIOns. These differences could be meaningful but the nature of our study, which was a qualitative method of research, does not allow definitive inference from the findings. In conclusion, RT in silu PCR as a qualitative method is able to localize mRNA gene expression in human breast lesions. In addition, mRNA expression levels are obviously different in benign tissues compared to malignant tissues. However, it is not possible to rely on the light differences between three malignant groups of our study. It is therefore necessary to do further investigations with quantitative research methods such as microarray analysis and or quantitative RT- PCR.